PENGARUH PRESTASI KERJA DAN LOYALITAS TERHADAP PROMOSI JABATAN (Studi Pada Karyawan Bagian Sales Executive and Counter Pada PT. Agung Automall Cabang Pekanbaru) - Alia Dwi Siska; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study used 3 variables, namely : Job Performance, Loyalty, and PromotionPosition. On the Variables of Work Achievement has 4 dimensions of Skills and Skills,Discipline, Personality, and Responsibility. In the Loyalty variable has 6 dimensions that areobedient to the rules, Responsibility to the Company / Organization, Willingness tocooperate, Ownership, Interpersonal relationships, and likes to work. On variablesPromotion Position has 3 Dimensions of Education, Experience, and Initiative and Creative.Objects in this study Are employees of the Sales Executive and Counter at PT. AgungAutomall Pekanbaru amounting to 41 employees. The analysis used in this research isValidity Test, Reliability Test, Simple Linear Regression, Multiple Linear Regression,Determination Test (R2), Individual Significant Test (t test) and Significant Test (f test).The result showed the influence of Work Achievement and Loyalty to PromotionPosition. The Better Job Performance and Employee Loyalty then the more likely to bepromoted higher positions. Subsequently, the resulted data from quisioner is calculate andtested with statistics through SPSS program. The calculated results is known that R Square isabout 0,419. It is meaned that the influence of variable Job Performance, and Loyaltyvariables was 41.9% to Job Promotion variables.Keywords : Job Performance, Loyalty, Job Promotion